Adapting to vision changes: nighttime driving experiences of older adults - Rundus, Christopher R.M.; Rose, Dominique; Zhang, Fangda; Brown, Sean; Yang, Jingzhen (Frontiers in Aging, 2025)
IntroductionThis qualitative study explored older adults’ perspectives and experiences of nighttime driving, focusing on age-related vision changes.MethodsWe conducted virtual, semi-structured interviews with active drivers aged 60 or older from central Ohio. The interview guide encompassed four key domains: personal and driving history, nighttime driving practices/abilities/anxieties, the role of driving, and policy opinions. Interviews were transcribed verbatim and analyzed using thematic analysis with ATLAS.ti™.ResultsEleven participants (eight males; ages 64–77) completed interviews. Four major themes emerged: (1) age-related vision and driving changes, (2) nighttime driving patterns, (3) importance of driving, and (4) nighttime driving safety recommendations. Each theme included two to three subthemes, focusing on perceived impact of vision changes on nighttime driving ability and potential adaptive strategies to address these changes.DiscussionOur findings contribute to existing literature and may inform programs and technological advancements to enhance nighttime driving safety for this vulnerable population.